SYNTHESIS OF PLANT-MEDIATED SILVER NANOPARTICLES USING TYLOPHORA INDICA MERR. (PITTAKARI) LEAF EXTRACT AND EVALUATION OF ITS ANTIMICROBIAL AND ANTICANCER ACTIVITY - RADHIKA S. OKE,; REBECCA S. THOMBRE,; A. K. PANDE, (International Journal of Pharma and Bio Sciences, 2015)
Nanotechnology and nanoscience has got tremendous applications in different areas like catalysis, medicine, chemicals and electronics. Plant mediated synthesis of nanoparticles offers a single step, easy and extracellular synthesis of nanoparticles. In this method, synthesis of silver nanoparticles was done using aqueous leaf extracts of Tylophora indica Merr. The phytoconstituents and reducing compounds present in the leaf extract reduces aqueous silver chloride rapidly to nanosilver. The bio fabricated nanoparticles were confirmed by Surface Plasmon Resonance (SPR) as characterized by UV-vis spectrophotometry and Fourier transform infrared spectroscopy (FTIR). The morphology and size of the silver nanoparticles were determined by Scanning Electron Microscopy. The silver nanoparticles synthesized were found to be effective against selected gram positive and negative bacteria (Staphylococcus aureus, Bacillus subtilis, and Escherichia coli). Anticancer activity of the nanoparticles was also done in vitro using MTT assay and its IC50 dose was found out. The cell line used in this assay was a breast cancer cell line, MCF-7. Thus, the biosynthesized nanoparticles possess potential applications in medicine and pharmaceutical fields.